Selenium Homeostasis and Clustering of Cardiovascular Risk Factors: A Systematic Review - Gharipour, Mojgan; Sadeghi, Masoumeh; Behmanesh, Mehrdad; Salehi, Mansour; Nezafati, Pouya; Gharpour, Amin (Acta Biomedica Atenei Parmensis, 2017)
Selenium is a trace element required for a range of cellular functions. It is widely used for the biosynthesis of the unique amino acid selenocysteine [Sec], which is a structural element of selenoproteins. This systematic review focused on the possible relation between selenium and metabolic risk factors. The literature was searched via PubMed, Scopus, ISI Web of Science, and Google Scholar. Searches were not restricted by time or language. Relevant studies were selected in three phases. After an initial quality assessment, two reviewers extracted all the relevant data, whereas the third reviewer checked their extracted data. All evidence came from experimental and laboratory studies. Selenoprotein P is the best indicator for selenium nutritional levels. In addition, high levels of selenium may increase the risk of metabolic syndrome while the lack of sufficient selenium may also promote metabolic syndrome. selenium supplementation in subjects with sufficient serum selenium levels has a contrary effect on blood pressure, LDL, and total cholesterol. According to the bioavailability of different types of selenium supplementation such as selenomethionine, selenite and selenium-yeast, it seems that the best nutritional type of selenium is selenium-yeast. Regarding obtained results of longitudinal studies and randomized controlled trials, selenium supplementation should not be recommended for primary or secondary cardio-metabolic risk prevention in populations with adequate selenium status.